2018
DOI: 10.1007/s10461-018-2085-6
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent with HIV Viral Load > 1500 Copies/mL Among Persons Engaged in Continuity HIV Care in an Urban Clinic in the United States, 2010–2015

Abstract: Persons with HIV who have entered care but have viral load > 1500 copies/mL may be the source of the majority of new HIV infections in the United States. We followed patients engaged in continuity care in the Johns Hopkins HIV Clinical Cohort between January 2010 and August 2015. We estimated person-time spent with viral load > 1500 copies/mL while in care after antiretroviral therapy (ART) initiation, while in care, and while alive. Person-time was classified according to the most recent viral load measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Specifically, one cohort study saw increases in uptake in ART for women (aPR 1.15; 95% CI 1.06, 1.24) and men (aPR 1.06; 95% CI 1.01, 1.10) over the course of the study period (Hoots et al, 2017). In contrast, Lesko, et al, who reported outcomes stratified by gender and race found that white women had the lowest percentage of person‐time in care after ART initiation and that both white and Black women had the greatest percentage of person‐time in care with a detectable HIV viral load (>1500 copies/ml) compared to male counterparts (Lesko et al, 2018). That study, however, only displayed percentages of person‐time stratified by race and gender with ART and viral load outcomes, without conducting relevant multivariable analysis or testing for differences between the groups.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, one cohort study saw increases in uptake in ART for women (aPR 1.15; 95% CI 1.06, 1.24) and men (aPR 1.06; 95% CI 1.01, 1.10) over the course of the study period (Hoots et al, 2017). In contrast, Lesko, et al, who reported outcomes stratified by gender and race found that white women had the lowest percentage of person‐time in care after ART initiation and that both white and Black women had the greatest percentage of person‐time in care with a detectable HIV viral load (>1500 copies/ml) compared to male counterparts (Lesko et al, 2018). That study, however, only displayed percentages of person‐time stratified by race and gender with ART and viral load outcomes, without conducting relevant multivariable analysis or testing for differences between the groups.…”
Section: Resultsmentioning
confidence: 96%
“…Predisposing factors were not well measured or well represented across the studies with a few exceptions. Only one study stratified analysis by sex or gender but did not conduct analyses or provide effect estimates of engagement in care (Lesko et al, 2018). As a whole, measures and comparisons of race and ethnicity were also inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…This cutoff was selected as an established indicator of a low viral load where HIV transmission is unlikely to occur. 29 , 30 , 31 These measures were collected through patient records, which contained indicators unavailable through point-of-care data collection methods, such as laboratory test results. Medical record review used data from Kazakhstan’s National Electronic HIV Case Management System, a government-approved database for the collection, storage, transfer, and analysis of epidemiological, laboratory, and clinical data on all HIV-positive registered cases.…”
Section: Methodsmentioning
confidence: 99%
“…In a longitudinal study of patients in continuity care, the time spent with a viral load >1500 copies/mL was evaluated. Hazardous alcohol use, recent drug use, black race, and age were highly associated with failure to maintain an HIV <1500 copies/mL [130]. In the Women's Interagency HIV Study, heavy drinking was associated with failure to remain virally suppressed as well [26].…”
Section: Alcohol and Hivmentioning
confidence: 99%